Anticorrosive properties and rust conversion mechanism of phytic acid‐based surface tolerant coating. Issue 1 (15th October 2020) - Xu, Hao; Lu, Guangming; Liu, Shuan; Pu, Jibin; Tian, Shu; Mao, Chunlong; Chen, Shanjun
Abstract: A phytic acid‐based surface tolerant epoxy coating was prepared, and the effect of phytic acid on the corrosion resistance of the composite coating on rusty carbon steel substrate was investigated. The results showed that the low‐frequency impedance modulus of the composite coating on rusty carbon steel could reached 10 8 Ω·cm 2 order of magnitude after immersing for 480 h in 3.5 wt% NaCl solution. Compared with pure epoxy coating, the phytic acid‐based surface tolerant epoxy coating on the rusty substrate exhibited better corrosion resistance even if with some artificial defects in the composite coating. The protective performance of the composite coating mainly came from the formation of a stable iron phytate chelate in the reaction of phytic acid and rust. For the rusty carbon steel, the original Fe 3+ on its surface was also transformed by phytic acid penetrating to the interface between the coating and the substrate. Therefore, a dense film was formed with the reaction of phytic acid and rust on the substrates, and the dense film became a part of the whole paint film, which could improve the corrosion resistance of the surface tolerant coating.